Syrian Students' Participation in Higher Education in Turkey: An Institutional Perspective - Atesok, Zeynep Ozde (Istanbul University Press, 2020)
Since the onset of the Syrian civil war, which triggered one of the biggest human tragedies in recent history, more than six million people have fled the country seeking asylum in neighboring countries and beyond (UNHCR, 2020a). While many governments and the international community in general have failed to respond to this emerging humanitarian crisis, millions of Syrian refugees are being hosted in neighboring countries without future prospects as the unrest continues well into its ninth year. In the face of the rising and unprecedented challenge of mass exodus and protracted displacement, each country has been confronted with growing needs of the affected populations within its particular political, economic and social contexts. As children and youth are among the displaced majority, the need for education has attracted public attention. Efforts to ensure a 'no lost generation' climbed high on the international agenda in a very short time span. Education has emerged as a top priority in this context as an important tool of sustainable development, and therefore refugee protection, integration and empowerment. By framing this humanitarian crisis as an education crisis, the needs and challenges of Syrian students (e.g. low enrolment rates, inclusion in education systems struggling under ever increasing pressure) have been central concerns. Higher education has only recently become part of the discussion. Considering the estimated 100-200,000 Syrian youths (EU, 2016), who have had their higher education disrupted, and the upcoming generation providing access to higher education is one of the greatest challenges of displacement, both for the host countries and the refugees themselves. Despite being a fundamental human right, access to and participation in higher education among asylum seekers and refugees remain very low and strictly dependent on national contexts and priorities. Global average higher education enrolment rates of 3% compared with 37% for non-refugees clearly indicates the unmet demand for higher education in refugee contexts (UNHCR, 2019d). Furthermore, in the face of documented aspirations among refugee populations, knowledge and research related to higher education in refugee studies continue to be limited. As the biggest refugee host country since 2015, Turkey has faced enormous challenges with the arrival of millions of displaced people in a relatively short period. The total number of Syrians currently under the country's temporary protection scheme has reached 3.6 million. This figure does not take account of unregistered people nor the 110,000 who have been naturalized (Mültecider, 2020). A high proportion of this population (more than 1.6 million) is registered Syrian children under 18. Almost half a million, however, are youths aged 19-25 who are considered as university age (DGMM, 2020). Taking into consideration the relatively young Syrian population, although provision for education has long been among the priorities of the Turkish Government, meeting the demand of ever-increasing numbers has, and still does, weigh heavy on the government.